Impact of the Three Gorges Dam on the spawning stock and natural reproduction of Chinese sturgeon in the Changjiang River, China - 高欣 林鹏程 黎明政 段中华 刘焕章 (Chinese journal of oceanology and limnology, 2016)
Chinese sturgeon （Acipenser sinensis） is the flagship species of the Changjiang River. The migration route of this species is blocked by the first dam, the Gezhou Dam, and its reproduction is affected by the Three Gorges Dam （TGD）, one of the largest dams in the world. We studied the impact of the impoundment of the Three Gorges Reservoir （TGR） since 2003 on the spawning stock and the natural reproduction of the Chinese sturgeon by using our monitoring data from 1997 to 2013. Results indicate that TGR impoundment has delayed the first spawning dates of the fish from middle-late October to late November, decreased the amount of spawning activities from twice to only once each year, and significantly reduced egg production. In particular, the fish did not demonstrate any spawning activities in 2013. Therefore, TGR impoundment significantly affects the natural reproduction of the fish downstream of the TGD. The spawning stock size of the fish is also predicted to further decrease in the future, which will lead to a risk of population extinction. Ecological regulations must be imposed on decreasing the water temperature to 20℃ before mid-October and increasing water discharge downstream of the TGD in October to induce spawning of the Chinese sturgeon.